Offsetting deficit conceptualisations: methodological considerations for higher education research - Coleman, Lynn (Critical Studies in Teaching and Learning, 2023)
This paper contributes to the current introspection in the academic development community that critiques the persistent conceptualisations of students as deficient. Deficit discourses are also implicated in many of the student support, curriculum and pedagogic initiatives employed across the higher education sector. The argument developed here, unlike most of the existing debates which focus on pedagogic or institutional initiatives, explores how the research interests and methodological choices of academic developers and researchers could incorporate sensitivity against deficit conceptions and foster more contextualised accounts of students and their learning. This article uses an ethnographic study into the assignment practices of vocational higher education students to show how certain methodological and theoretical choices engender anti-deficit conceptualisations. The study’s analytic framework uses the concepts of literacy practices and knowledge recontextualisation to place analytic attention on both the students’ assignment practices and the influence of curriculum decision making on such practices.